ChemInform Abstract: Hydrogen Storage Properties of LaMgNi3.6M0.4 (M: Ni, Co, Mn, Cu, Al) Alloys. Issue 48 (2nd December 2014) - Yang, Tai; Zhai, Tingting; Yuan, Zeming; Bu, Wengang; Xu, Sheng; Zhang, Yanghuan
Abstract LaMgNi3.6M0.4 (M: Ni, Co, Mn, Cu, Al) alloys are prepared by induction melting of the elements.